2003
DOI: 10.1128/jb.185.11.3307-3316.2003
|View full text |Cite
|
Sign up to set email alerts
|

How Clonal Is Staphylococcus aureus ?

Abstract: Staphylococcus aureus is an important human pathogen and represents a growing public health burden owing to the emergence and spread of antibiotic-resistant clones, particularly within the hospital environment. Despite this, basic questions about the evolution and population biology of the species, particularly with regard to the extent and impact of homologous recombination, remain unanswered. We address these issues through an analysis of sequence data obtained from the characterization by multilocus sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
494
13
16

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(577 citation statements)
references
References 35 publications
47
494
13
16
Order By: Relevance
“…CC97 isolates have previously been reported to be obtained from humans (Feil et al, 2003). In Brazil CC97 and CC127 were predominant (Rabello et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…CC97 isolates have previously been reported to be obtained from humans (Feil et al, 2003). In Brazil CC97 and CC127 were predominant (Rabello et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance was determined using standard disk diffusion methods. The previously described 161 human S. aureus isolates were from a wide range of sources, representing the major dominant lineages of S. aureus from hospitals and the community, including hospital MRSA (Feil et al, 2003;.…”
Section: Methodsmentioning
confidence: 99%
“…However isolates of lineages isolated in the Essex region (RVC collection) were also found throughout the UK. The remaining bovine isolates were assigned to ST130 (n52), reported previously in cows and a goat from Norway (Jørgensen et al, 2005); ST188 (n53), found in humans at low frequency (Feil et al, 2003); ST1 (n51) a dominant human lineage (Feil et al, 2003); and one orphan.…”
Section: Distribution Of Animal Lineagesmentioning
confidence: 99%
“…The key factors in the evolutionary response of pathogens to their environments can be measured by assessing the genetic diversity (and partitioning of that diversity within versus between populations), the impact of natural selection in shaping that diversity, and the impact of recombination in redistributing that diversity, sometimes into novel combinations. Population studies of pathogens using multilocus sequencing typing (MLST) methods are generally aimed at inferring genetic diversity (usually estimated as the relative contribution of recombination and mutation per allele or per site), selection pressure, and population structure Maynard-Smith et al, 2000;Dingle et al, 2001;Feil et al, 2003;Meats et al, 2003;Viscidi and Demma, 2003) to study the relative impact of genetic drift and natural selection on the evolutionary history of these pathogens.…”
Section: Introductionmentioning
confidence: 99%